Effet Antidiabétique et cicatrisant du miel de la région de Djelfa « Étude in vivo » - Kharroubi, Yasmina; Ougab, Assia (My University, 2020)
Diabetes is a metabolic disorder characterized by the presence of hyperglycemia due to reduction in insulin secretion or insulin action, or both. Honey has been used in traditional medicine for a long time, but the health benefits have been explained in recent decades, when the scientific world was concerned with testing and thus explained the benefits of honey. Different studies prove its role in diabetic patients. Our work is based on the evaluation of the anti-diabetic effect and wound healing activity of Sidir honey from the Djelfa region "in vivo study" in rats made diabetic by Streptozotocin (STZ), 60 mg / kg for the wound healing activity and 65 mg / kg for antidiabetic activity by a single dose intraperitoneal (IP) route. During 28 days of the honey-based treatment at different doses (5, 10 and 20%) for the test of the antidiabetic activity on diabetic rats and for 13 days for the wound healing effect of honey (Sidir) on diabetic and non-diabetic rats. Before diabetes induction, there was a stable blood sugar level in all rats. After the induction of diabetes there was a significant increase in blood glucose in diabetic rats (48h after injection of STZ), and a decrease in body weight, in comparison with non-diabetic control rats. Concerning the antidiabetic activity, the results obtained show a more effective effect of honey and presents a natural treatment with hypoglycemic and hypocholesterolemia properties as well as the improvement of the enzymatic activity, namely the transaminases, having the possibility of treating diabetes and its complications, on the other hand treatment with Metformin® has shown undesirable effects on the liver which results in increased transaminase (TGO and TGP). Regarding the wound healing effect of honey we see an improvement in the use of honey as a wound healing agent in diabetics. These results strongly resemble that of the results obtained with Madécassol®.
Keywords: Sidir honey; Metformin®; Antidiabetic activity; wound healing effect; In Vivo.